Comparison of plasma vitamin D levels in patients with Sjögren's syndrome and healthy subjects. (28th January 2014) - Erten, Şükran; Şahin, Ali; Altunoğlu, Alpaslan; Gemcioğlu, Emin; Koca, Cemile
Abstract Aim Sjögren's syndrome (SS) is a systemic autoimmune disease characterized by chronic inflammation of the salivary and lacrimal glands. There is increasing evidence indicating that vitamin D is important in the initiation and propogation of a range of autoimmune diseases which may include SS. The aim of the present study was to evaluate plasma vitamin D (vit D) levels in patients with SS and to compare this with a control group. Method One hundred and seven SS patients (97 [90.7%] female and 10 [9.3%] male) and 74 healthy controls (64 [86.5%] female and 10 [13.5%] male) were included into the study. Plasma baseline 25‐hydroxy‐vit D levels were measured by high‐powered liquid chromatography method using an Agilent 1100 liquid chromatograph. Results Plasma vit D levels in SS patients (20.5 ± 10.5 μg/L) were significantly lower than in the control group (28.4 ± 15.2 μg/L) (P < 0.001). Female SS patients had significanly lower vit D levels (19.3 ± 9.3 μg/L) than controls (28.3 ± 15.8 μg/L) (P < 0.001) but this difference was not present among the male patients and controls. There was no correlation between plasma vit D levels and erythrocyte sedimentation rate and C‐reactive protein in SS patients. Conclusion Vit D deficiency was frequent in patients with SS. In particular, female SS patients had the risk of vit D deficiency. It may be convenient to look for vit D deficiency and to correct vit D nutritional status in SS patients.